CRITERIA, INDICATORS AND LAWS OF SMALL BUSINESS DEVELOPMENT - Israilov, Rusrambek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The possibility of increasing the efficiency of entrepreneurial activity depends on the level of substantiation of strategic directions in the field of production of competitive products and the organization of their introduction to the market in accordance with the logic of economic actions in dynamic market conditions. The process of economic reform is aimed at developing market infrastructure, intensifying competition and the manifestation of its stimulating innovative properties, forming effective mechanisms for the structural restructuring of the national and regional economy, creating sustainable production and market communications, as well as promoting entrepreneurship.